2014
DOI: 10.1155/2014/524757
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis to Sartorius Muscle from a Muscle Invasive Bladder Cancer

Abstract: Bladder cancer constitutes the ninth most common cancer worldwide and approximately only 30% of cases are muscle invasive at initial diagnosis. Regional lymph nodes, bones, lung, and liver are the most common metastases from bladder cancer and generally from genitourinary malignancies. Muscles constitute a rare site of metastases from distant primary lesions even though they represent 50% of total body mass and receive a large blood flow. Skeletal muscles from urothelial carcinoma are very rare and up to date … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…However, clinical reports only rarely document events of tumor metastasis occurring in skeletal muscles. So far, tumor metastasis in muscle tissue have been reported only in a few cases of laryngeal squamous carcinoma, 35-37 lung cancer, 38 papillary thyroid cancer, 39 bladder cancer, 40 and gastrointestinal stromal tumor. 41 , 42 …”
Section: Discussionmentioning
confidence: 99%
“…However, clinical reports only rarely document events of tumor metastasis occurring in skeletal muscles. So far, tumor metastasis in muscle tissue have been reported only in a few cases of laryngeal squamous carcinoma, 35-37 lung cancer, 38 papillary thyroid cancer, 39 bladder cancer, 40 and gastrointestinal stromal tumor. 41 , 42 …”
Section: Discussionmentioning
confidence: 99%
“…Muscles are an unusual site of metastases even though they represent almost 50% of the total body mass [ 3 ] and are highly vascularized [ 4 ]. Several defensive factors have been proposed to create a hostile environment against metastases such as muscle pH, muscle motion, and ability to remove lactic acid accumulation that plays a role against tumor neovascularity [ 6 8 ]. Magee and Rosenthal [ 9 ] in 2002 reported that a previously documented local trauma seems to be a risk factor for development of metastasis, probably for an imbalance of local physiological and mechanical factors.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscles metastases from UCC are, however, very rare and to our best knowledge, only 9 cases have been reported in the English literature [ 2 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations